Learning to read critically in teaching and learning - Poulson, Louise; Wallace, Mike, 1950- (SAGE, 2004)
Combining a teaching text with exemplary reports of research and a literature review conducted by international scholars this collection addresses the critical analysis of texts and the methods used to incorporate such analysis into literature reviews.
Keywords: Education -- Research.; Teaching -- Research.; Learning -- Research.; Criticism.; Apprentissage -- Recherche.; Critique.; EDUCATION -- Research.; Criticism; Education -- Research; Learning -- Research; Teaching -- Research; Kritisches Denken; Lesen; Unterricht; Wissenschaftliche Literatur; Literatuuronderzoek.; Onderwijskunde.